A Transcription System from MusicXML Format to Braille Music Notation. (21st December 2006) - Goto Goto, D. D.; Gotoh Gotoh, T. T.; Minamikawa-Tachino Minamikawa-Tachino, R. R.; Tamura Tamura, N. N.
Abstract : The Internet enables us to freely access music as recorded sound and even music scores. For the visually impaired, music scores must be transcribed from computer-based musical formats to Braille music notation. This paper proposes a transcription system from the MusicXML format to Braille music notation using a structural model of Braille music notation. The resultant Braille scores inspected by volunteer transcribers are up to the international standard. Using this simple and efficient transcription system, it should be possible to provide Braille music scores via the Internet to the visually impaired.